Photojournalism: a social semiotic approach - Caple, Helen; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2013)
This book explores the role of photographs in newspapers and online news, analyzing how meanings are made in images and exploring text-image relations, illustrated with authentic news stories from both print and online news outlets.
Keywords: Culture -- Study and teaching; Communication; Linguistics; Discourse analysis; Journalism; Cultural and Media Studies; Media Studies; Linguistics, general; Journalism; Media and Communication; Discourse Analysis; Communication Studies